2019
DOI: 10.14221/ajte.202v45n12.2
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Teachers Beliefs On The Gap Between Educational Research And Practice

Abstract: Teachers' beliefs towards educational research has become one significant factor in explaining the gap between research and practice. The present study aimed at reviewing the scale to measure teachers' beliefs about the causes and problems related to research-based practices, describing beliefs that teachers appear to hold, and examining its relation to their demographic characteristics. The study involved 466 in-service teachers in Jakarta Province. The study employed the 24-item scale developed by Broekkamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Various studies have shown that between perspectives, views and attitudes regarding educational research, a clear line can be drawn (Beycioglu et al, 2010;Drill et al, 2013;Guilfoyle et al, 2020;Ismail et al, 2019;Leat et al, 2014;Peiser et al, 2022;Purnomo, Pramudiani, et al, 2020;Purnomo, Prananto, et al, 2020). This is because belief itself involves these two components, both the affective domain and the cognitive domain (Purnomo, Suryadi, & Darwis, 2016;Purnomo, Pramudiani, et al, 2020). In this study, the perspective on educational research is seen in terms of the two affective and cognitive components which are inseparable, influence each other and overlap.…”
Section: ▪ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies have shown that between perspectives, views and attitudes regarding educational research, a clear line can be drawn (Beycioglu et al, 2010;Drill et al, 2013;Guilfoyle et al, 2020;Ismail et al, 2019;Leat et al, 2014;Peiser et al, 2022;Purnomo, Pramudiani, et al, 2020;Purnomo, Prananto, et al, 2020). This is because belief itself involves these two components, both the affective domain and the cognitive domain (Purnomo, Suryadi, & Darwis, 2016;Purnomo, Pramudiani, et al, 2020). In this study, the perspective on educational research is seen in terms of the two affective and cognitive components which are inseparable, influence each other and overlap.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…However, in the school context, learning practices are very often not in line with the results of educational research (Awang-hashim et al, 2019;Kaur et al, 2020;Purnomo, Pramudiani, et al, 2020). This shows that there is a gap between the results of educational research and the learning practices carried out by teachers (Purnomo, Pramudiani, et al, 2020).…”
Section: ▪ Introductionmentioning
confidence: 99%
See 3 more Smart Citations